Gaze cues vs. arrow cues at short vs. long durations. Issue 9 (21st October 2022) - Singh, Tarini; Schöpper, Lars-Michael; Domes, Gregor; Frings, Christian
ABSTRACT: Information processing is more efficient at cued relative to non-cued locations. A number of studies have examined whether non-predictive gaze cues are special due to their biological relevance. While most studies indicate that cueing effects of gaze cues and arrow cues are similar, one aspect remains to be examined – cue duration. Contrary to early findings, a number of studies have observed cueing effects at short durations for arrow cues. For gaze cues however, the evidence is more mixed. The present study therefore aims to directly compare the cueing effects of arrow and gaze cues at short and long durations. Participants ( N = 30) performed a discrimination task and were presented with arrow and gaze cues for short or long durations. Cueing effects were measured at each duration for each cue type. Significant cueing effects were observed for both cue types at both short and long duration. Moreover, for both cue types, no difference was observed in the magnitude of cueing effects at short and long duration. The results suggest that both cue types cues can efficiently orient attention even at short cue durations, and that the biological relevance of gaze direction cues do not provide any advantage over arrows.